Factors associated with motherhood among urban refugee adolescent girls and young women in informal settlements in Kampala, Uganda. (2nd January 2023) - Malama, Kalonde; Logie, Carmen H.; Okumu, Moses; Hakiza, Robert; Mwima, Simon; Kyambadde, Peter
ABSTRACT: Adolescent girls and young women (AGYW) in sub-Saharan Africa face a high risk of unintended pregnancy. This risk is compounded in informal settlements, where resources are scarce and access to sexual and reproductive health services is limited. Being a young mother in informal settlements could exacerbate existing experiences of resource scarcity and poor access to sexual and reproductive health services. To explore this, we analyzed the factors associated with motherhood among refugee AGYW in Kampala, Uganda. Between January and March 2018, peer researchers recruited refugee youth aged 15–24 and living in five informal settlements in Kampala to participate in this study. We used a backwards generalized linear model with a log binomial regression to determine if mental health, resource insecurity and sexual and reproductive health variables were associated with motherhood among study participants. Our analysis included 333 AGYW with a mean age of 19.3 years (standard deviation: 2.6). Nearly one-quarter (23 percent; n = 76) of AGYW had children. Having children was associated with greater likelihood of reporting food insecurity (adjusted prevalence ratio [aPR]: 1.96, 95 percent confidence interval [CI]: 1.07–3.61), depressive symptoms (aPR: 2.03, 95 percent CI: 1.09–3.80), and contraception uptake (aPR: 2.37, 95 percent CI: 1.58–3.56) compared to not having children. Mental health and resource insecurity interventions are required for refugee AGYW with children in informal settlements. Sexual and reproductive health services should be promoted to refugee AGYW regardless of motherhood status to prevent unplanned pregnancy.